IDENTIFYING NIGERIA’S NATURAL RATE OF UNEMPLOYMENT: PRELIMINARY EVIDENCE FROM THE AUGMENTED PHILLIPS RELATION - Oyefusi, Aderoju; Arodoye, Nosakhare (University of Nigeria Journal of Political Economy, 2021)
Concern and anxiety over the rising level of unemployment in Nigeria, especially among the youths, have mounted over the last decade. This concern will be misplaced, however, if we do not know the country’s “natural” rate of unemployment. This paper attempts to identify Nigeria’s “natural” unemployment rate and its evolution over time using the framework of the expectation-augmented Phillips relation and based on estimated parameters by the International monetary Fund (IMF) and historical data from the IMF and the National Bureau of Statistics (NBS). The results show that the rate may have risen significantly over time. This has implications for our understanding of the Nigerian labour market and the unemployment situation, the role and limit of macroeconomic policies, and the prospects of long-term growth in the country. While it is too early to make categorical statements on the reasons for the sharp increases in the “natural” unemployment rate, the paper draws attention to the possible influences of a strong social insurance around family networks (in particular, remittance inflows) and income from illicit “businesses” on the willingness to participate in the labour market at existing wage levels, and the likely impact of price increases arising from the unregulated nature of the country’s product market. The paper concludes with the need for a more rigorous study of the labour market and the dynamics of change over the past twenty to thirty years.